Reminiscence respecified: A conversation analytic examination of practice in a specialist dementia care home - Felicity Slocombe; Elizabeth Peel; Alison Pilnick; Saul Albert (Elsevier, 2024)
Although discussion of reminiscence is prevalent in dementia care research, few studies have examined what actually occurs in these interactions, and how they are structured. This study examined how reminiscence activities are structured and negotiated in a care home environment. Informal one-to-one reminiscence interactions between people living with dementia and professional carers were transcribed from a larger video dataset. We used Conversation Analysis to examine reminiscence sequences in a novel relational approach that explored the interactional practices used by carers and people living with dementia. We identified divergences between manualised practice recommendations and observed interactional practices, such as the rarity of open questions, and frequent use of closed questions. This was contrary to current practice recommendations. These and other divergences demonstrate the value of interactional research in informing reminiscence practice and training manuals. By examining how reminiscence operates in practice, our approaches to conducting such activities can be more empirically informed. Our findings can be used to advise and guide those doing reminiscence work in care home settings, and improve the inclusiveness of reminiscence interactions. Through incorporating empirically informed techniques that both carers and people with dementia use in practice, we can facilitate interactions around memories which are supportive of people with dementia's identity.